Doctor Strange. 1, The way of the weird - Aaron, Jason (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2016)
Only Doctor Strange can protect our world from the darkness beyond - now, witness the full toll that constant struggle takes on Earth's Sorcerer Supreme! Every spell cast comes at a cost, but what happens when Strange falls behind on his tab? Find out as the good doctor wakes up somewhere very odd, nearly naked - with no spell books, no weapons and no memory of how he got there...or why all the monsters are chasing him! And as a new visitor to Strange's Sanctum Sanctorum learns one wrong door can lead to oblivion, a magic circle of Strange's friends and allies are about to face their greatest threat. Dark forces are destroying everything mystical in the multiverse, and their sights are set on this dimension. Magic's days are numbered, and Doctor Strange is not ready!